The administratization of criminal convictions worldwide: History, extent, and consequences - Gabriele Paolini (University of Hamburg, Institute of Law and Economics (ILE), 2023)
A global trend towards the imposition of criminal convictions without trial has been described as one of the key features of contemporary criminal procedure. Such phenomenon is referred to as "administratization" of criminal convictions, and it is characterized by the reliance on plea bargaining and penal orders as ordinary means for disposing of criminal cases. The present paper first describes the history, current adoption, and variations in the legal design of such procedures. Later, it provides original data about the extent of administratization of criminal convictions in fifty-nine jurisdictions worldwide. Finally, it discusses possible beneficial and adverse effects of higher administratization rates on key aspects of criminal justice systems, and the challenges to the empirical assessment of such effects.
Keywords: 330